Virtual corporeality and aesthetic experience. Issue 1 (1st June 2017) - Sousa, Catarina Carneiro de
The experience of the body in the Metaverse is not always an experience of the flesh, at least regarding the avatar. Even though virtual experiences can trigger a physical dimension of the senses, these sensations are lived by the body in front of the screen, rather than by the avatar's body, which may function as an expressive element. The avatar may be crucial in communicating with others (as language) and play a role in the users' access and interaction with the virtual world (as experience). A tension between language and experience opens up a new and fundamental aesthetic territory in the avatar, demanding a reconfiguration of concepts and processes involved in its creation and embodiment. This article aims to explore how virtual corporeality may emerge from this tension in the manipulation of avatars in Creative Collaborative Virtual Environments (CCVE), what affordances enable this emergence and how it impacts aesthetic and creative experience.